A Kinetic Model for Blood Biomarker Levels After Mild Traumatic Brain Injury - Azizi, Sima; Hier, Daniel B.; Allen, Blaine; Obafemi-Ajayi, Tayo; Olbricht, Gayla R.; Thimgan, Matthew S.; Wunsch, Donald C. (Frontiers in Neurology, 2021)
Traumatic brain injury (TBI) imposes a significant economic and social burden. The diagnosis and prognosis of mild TBI, also called concussion, is challenging. Concussions are common among contact sport athletes. After a blow to the head, it is often difficult to determine who has had a concussion, who should be withheld from play, if a concussed athlete is ready to return to the field, and which concussed athlete will develop a post-concussion syndrome. Biomarkers can be detected in the cerebrospinal fluid and blood after traumatic brain injury and their levels may have prognostic value. Despite significant investigation, questions remain as to optimal sampling times and preferred cut-off levels. Modeling the kinetic behavior of these biomarkers could inform answers to these questions. We propose a one-compartment kinetic model for S100B, UCH-L1, NF-L, GFAP and tau biomarker levels after mild TBI based on accepted pharmacokinetic models for oral drug absorption. We approximated model parameters using previously published studies. Since parameter estimates were approximate, we did uncertainty and sensitivity analyses. Using estimated kinetic parameters for each biomarker, we applied the model to an available post-concussion biomarker dataset of UCH-L1, GFAP, tau and NF-L biomarkers levels. Implications for the use of blood biomarkers for the diagnosis of mild TBI are discussed.